Increased expression of plasma mir-9-3p and let-7b-3p in methamphetamine use disorder and its clinical significance - Wei Wang; Chen Li; Guangsheng Sun; Cunxi Qiu; Junyi Fan; Yuhan Jin; Kunpeng Liu; Peng Sun (Scientific Reports)
Abstract Methamphetamine use disorder has emerged as a significant public health concern globally. This study endeavors to elucidate the alterations in expression changes of miRNAs in the plasma of methamphetamine use disorder and elucidate the alterations in miRNA expression in the plasma of individuals with methamphetamine use disorder and investigate the relationship between these differentially expressed miRNAs and the disorder itself, cravings for methamphetamine, and associated mental disorders. Furthermore, the study seeks to clarify the expression of downstream target molecules of specific miRNAs in the plasma of methamphetamine use disorder, assess the diagnostic utility of these miRNAs and their target molecules, explore their potential as biomarkers, and identify potential targets for the diagnosis and treatment of methamphetamine use disorder. The research subjects included 112 individuals with methamphetamine use disorder and 112 healthy controls. A questionnaire was utilized to gather baseline information on methamphetamine use disorder, assess craving for methamphetamine using a Visual Analog Scale (VAS), and evaluate anxiety (SAS) and depression (SDS) states. Employing qRT-PCR technology, we measured the expression levels of miR-9-3p and let-7b-3p in the plasma of those with the disorder. Bioinformatics tools were then used to predict downstream target molecules. Western blot analysis was conducted to quantify the levels of these target molecules in the plasma. Receiver operating characteristic (ROC) curves were utilized to evaluate the diagnostic accuracy of miRNAs and their target molecules. Additionally, we analyzed the correlation between the miRNA expression levels and the psychiatric symptoms of methamphetamine use disorder. The qRT-PCR results revealed that the expression levels of miR-9-3p and let-7b-3p were significantly elevated in the plasma of individuals with methamphetamine use disorder compared to healthy controls (P < 0.05). Furthermore, qRT-PCR and Western blot analyses demonstrated that transfection with miR-9-3p mimic led to overexpression of miR-9-3p, while transfection with let-7-3p mimic promoted overexpression of let-7-3p, concurrently inhibiting the protein levels of BDNF and GSK3B in cells (P < 0.05); ROC curve analysis indicated that the AUC for miR-9-3p was 0.782 (95% CI 0.716–0.848) and for let-7b-3p was 0.720 (95% CI 0.650–0.789). However, Spearman correlation analysis showed no significant association between the expression levels of target miRNAs and proteins and the psychiatric symptoms of methamphetamine use disorder. Notably, the combination of miR-9-3p, let-7b-3p, and BDNF exhibited high diagnostic accuracy for methamphetamine use disorder, suggesting their potential as biomarkers for its diagnosis.